2020
DOI: 10.4048/jbc.2020.23.e15
|View full text |Cite
|
Sign up to set email alerts
|

Anastomosing Hemangioma of the Breast: An Unusual Case at an Unusual Site

Abstract: Anastomosing hemangioma (AH) is an unusual benign vascular lesion that commonly occurs in the kidney and genitourinary tract. We report a case of AH in a 49-year-old woman presenting as a mass in the breast, a site which, to the best of our knowledge, has not been previously documented in the English literature. Microscopic examination of the mass revealed a well-demarcated proliferation of anastomosing vascular spaces lined by bland endothelial cells, with focal hobnailing and scattered intravascular fibrin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…ERG is also an endothelial marker, but it is more specific and sensitive than CD31 or CD34. ERG (+) has also been reported previously in AH patients (15,16,30,40,44,53). As spindle stromal cell hyperplasia was observed within the spermatic cord, we stained the markers of spindle cell sarcoma (e.g., rhabdomyosarcoma, leiomyosarcoma, regressed germ cell tumors, and MPNST), such as desmin, inhibin-α, S-100, and NSE.…”
Section: Discussionsupporting
confidence: 78%
“…ERG is also an endothelial marker, but it is more specific and sensitive than CD31 or CD34. ERG (+) has also been reported previously in AH patients (15,16,30,40,44,53). As spindle stromal cell hyperplasia was observed within the spermatic cord, we stained the markers of spindle cell sarcoma (e.g., rhabdomyosarcoma, leiomyosarcoma, regressed germ cell tumors, and MPNST), such as desmin, inhibin-α, S-100, and NSE.…”
Section: Discussionsupporting
confidence: 78%
“…Angiosarcoma was excluded because of no well-formed vascular channels in this case, although very high MIB-1 index indicated that the tumor cells were mitotically active like angiosarcoma. 18) Hemangioma was also excluded based on very high MIB-1 index and no areas of the so-called tombstoning. The tumor in this case might arise from blood vessels on the pial surface of the spinal cord because the tumor existed extra-pially and was easily separated from the arachnoid membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when vascular tumors composed of anastomosing channels are encountered in the breast and are of small size, showing circumscription, and with no significantly atypical cytology, a conservative diagnosis of anastomosing hemangioma is recommended with complete excision and close clinical follow-up. 29 Recent studies have found GNAQ- activating mutations in anastomosing hemangiomas. 31 Although GNA14, GNA11 , and GNAQ mutations have also been described in other benign vascular lesions but not in malignant vascular tumors.…”
Section: Anastomosing Hemangiomamentioning
confidence: 99%
“…Relatively well-circumscribed proliferation of anastomosing vascular channels with lobular or diffuse growth patterns. [28][29][30] It is an unusual lesion as a significant anastomosis between the vascular spaces is not a feature seen in hemangioma and is a feature usually seen in angiosarcoma only. The endothelial cells lining the vascular spaces often show hobnailing with minimal to no cytologic atypia or mitotic activity.…”
Section: Microscopic Featuresmentioning
confidence: 99%